The Association between Stress Measured by Allostatic Load Score and Physiologic Dysregulation in African Immigrants: The Africans in America Study - Brianna A Bingham; Michelle T Duong; Madia Ricks; Lilian S Mabundo; Rafeal L Baker; Jean N Utumatwishima; Margaret Udahogora; David Berrigan; Anne E Sumner (Frontiers Media S.A., 2016)
Introduction: Allostatic load score (ALS) summarizes the physiological effect of stress on cardiovascular, metabolic and immune systems. As immigration is stressful, ALS could be affected.Objective: Associations of age of immigration, reason for immigration and unhealthy assimilation behavior with ALS were determined in 238 African immigrants to the United States (US) (age 40±10, mean±SD, range 21-64y). Methods: ALS was calculated using ten variables from three domains; cardiovascular (SBP, DBP, cholesterol, triglyceride, homocysteine), metabolic (BMI, A1C, albumin, eGFR) and immunological (hsCRP). Variables were divided into sex-specific quartiles with high-risk defined as the highest quartile for each variable except for albumin and eGFR which used the lowest quartile. One point was assigned if the variable was in the high-risk range and zero if not. Unhealthy assimilation behavior was defined by a higher prevalence of smoking, alcohol consumption or sedentary activity in immigrants who lived in the US for ≥10y compare to <10y.Results: Sixteen percent of the immigrants arrived in the US as children (age<18y); 84% arrived as adults (age≥18y). Compared to adulthood immigrants, childhood immigrants were younger (30±7 vs. 42±9, P<0.01), but had lived in the US longer (20±8 vs. 12±9y, P<0.01). Age-adjusted ALS were similar in childhood and adulthood immigrants (2.78±1.83 vs. 2.73±1.69, P=0.87). For adulthood immigrants, multiple regression analysis (adjR2=0.20) revealed older age at immigration and more years in the US were associated with higher ALS (both P<0.05); whereas current age, education, income and gender had no significant influence (all P≥0.4). The prevalence of smoking, alcohol intake and physical activity did not differ in adulthood immigrants living in the US for ≥10y vs. <10y (all P≥0.2). Reason for immigration was available for 77 participants. The reasons included: family reunification, lottery, marriage, work, education and asylum. Compared to all other reasons combined, immigration for family reunification was associated with the lowest ALS (1.94±1.51 vs. 3.03±1.86, P=0.03).Conclusions: African immigrants do not appear to respond to the stress of immigration by developing unhealthy assimilation behaviors. However, older age at immigration and increased duration of stay in the US are associated with higher ALS; whereas family reunification is associated with lower ALS.